He’s a Lunatic! Il caso Herman Merivale - Maria Serena Marchesi (Lea, 2022)
The essay analyses the case of Herman Charles Merivale (1839-1906), a brilliant playwright and novelist whose struggles with mental illness often forced him into a painfully marginalized position in the literary milieu in which he moved. It focuses on how Merivale thematized the relationship between madness and society in his literary works, such as the tragedy Ravenswood (1882), his farce He’s a Lunatic! (1867), and his autobiographical pamphlet My Experiences in a Lunatic Asylum. By a Sane Patient (1879), and how he re-elaborated within the comic frame the theme of the pervasive perception of madness in Victorian society.